Fundamental Studies on the Electrocatalytic Properties of Metal Macrocyclics and Other Complexes for the Electroreduction of o2 - Zagal-Moya, J; Zagal-Moya, J (2013)
The high prospects of exploiting the oxygen reduction reaction (ORR) for lucrative technologies, for example, in the fuel cells industry, chlor-alkali electrolysis, and metal-air batteries, to name but a few, have prompted enormous research interest in the search for cost-effective and abundant catalysts for the electrocatalytic reduction of oxygen. This chapter describes and discusses the electrocatalysis of oxygen reduction by metallomacrocyclic complexes and the prospect of their potential to be used in fuel cells. Since the main interest of most researchers in this field is to design catalysts which can achieve facile reduction of O2 at a high thermodynamic efficiency, this chapter aims to bring to light the research frontiers uncovering important milestones towards the synthesis and design of promising metallomacrocyclic catalysts which can accomplish the four-electron reduction of O2 at low overpotential and to draw attention to the fundamental requirements for synthesis of improved catalysts. Particular attention has been paid to discussion of the common properties which cut across these complexes and how they may be aptly manipulated for tailored catalyst synthesis. Therefore, besides discussion of the progress attained with regard to synthesis and design of catalysts with high selectivity towards the four-electron reduction of O2, a major part of this chapter highlights quantitative structure-activity relationships (QSAR) which govern the activity and stability of these complexes, which when well understood, refined, and carefully implemented should lead to rational design of better catalysts. A brief discussion about nonmacrocyclic copper (I) complexes, particularly Cu(I) phenanthrolines, and those with a laccase-like structure which exhibit promising activity for ORR has been included in a separate section at the end. © Springer-Verlag London 2013.